Manajemen Pendidikan Inklusif di Sekolah Dasar - Kurniawan, Asep - (IAIN Syekh Nurjati Cirebon, 2021)
The purpose of this paper was to describe the management of inclusive education in state primary school Gunung Sari Dalam. This was descriptive qualitative research. Data collection techniques are in-depth observation, in-depth interviews and documentation. Testing the validity of the data used source and method triangulation. The analysis was carried out through data collection, data reduction, data display, and data conclusion. The finding was the management of inclusive education at Elementary School Gunung Sari Dalam was carried out in accordance with the appropriate stages. Student management began with planning for new student admissions. The implementation was through the inclusion stage, the identification and assessment of the school, however, did not involve experts. The school used a modified 2013 curriculum. The learning process management was begun by analyzing the learning objectives.Â The teacher also adapted learning and evaluation to the conditions of students. In addition, teacher management was begun by list of teacher needs, recruitment and selection according to special educational backgrounds. The division of special teacher work rested on agreement and coordination. Facilities and infrastructure management was carried out through planning based on a needs analysis and procurement.